Hubungan Penggunaan Smartphone Terhadap Perkembangan Sosial Emosional Anak Usia Dini - Christantya, Maria; Rofiyarti, Fitri (Universitas Narotama, 2023)
ABSTRACT Maria Christantya: The Relationship between Smartphone Use and Social Emotional Development in Early Childhood. Thesis. Surabaya: Early Childhood Education Study Program, Faculty of Teacher Training and Education, Narotama University, 2023. This study aims to examine the relationship of smartphone use to children's social emotional development and to review journals related to the relationship of smartphone use to early childhood social development. The design of this study uses a design based on the characteristics of the main research problem, namely the associative strategy. Associative research is research that aims to determine the effect of two or more variables where these results are obtained by analyzing the relationship between smartphone use and social emotional development in early childhood in Surabaya. The cross-sectional research design is a measurement or observation of the independent variables and the dependent variable only once at a time. The results of this study show that the results of the correlation test show that the correlation coefficient is 1.632 and a significant value is 0.006 (p <0.05). These results indicate that the hypothesis is accepted or there is a relationship between smartphone use and early childhood social emotional development. The Effect of Using a Smartphone on Social Emotional Development is 26%. Meanwhile, 74% of Children's Social Emotional Development is influenced by other variables.